2008
DOI: 10.1021/la802820u
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Wilhelmy and Related Liquid Property Measurements Using Constant-Diameter Nanoneedle-Tipped Atomic Force Microscope Probes

Abstract: The micro-Wilhelmy method is a well-established method of determining surface tension by measuring the force of withdrawing a tens of microns to millimeters in diameter cylindrical wire or fiber from a liquid. A comparison of insertion force to retraction force can also be used to determine the contact angle with the fiber. Given the limited availability of atomic force microscope (AFM) probes that have long constant diameter tips, force-distance (F-D) curves using probes with standard tapered tips have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 28 publications
7
102
0
Order By: Relevance
“…Both measurements reveal the dramatic increase in damping followed by a progression to a steady-state value which is determined by the viscous damping of the probe oscillation. Similar overlap of the Q and rms curves is obtained when one raises the probe from the surface to break through the water-air interface at H ϳ500 m. However, in this case as more of the vertical part of the probe emerges from the water it effectively drags a progressively larger column of water which adheres to the flat end portion of the probe 21 ͑i.e., h max ϳ 2 times fiber diameter͒ creating the hysteresis effect shown in Fig. 3 for the high-k probe.…”
Section: Probe Damping In Watersupporting
confidence: 54%
See 4 more Smart Citations
“…Both measurements reveal the dramatic increase in damping followed by a progression to a steady-state value which is determined by the viscous damping of the probe oscillation. Similar overlap of the Q and rms curves is obtained when one raises the probe from the surface to break through the water-air interface at H ϳ500 m. However, in this case as more of the vertical part of the probe emerges from the water it effectively drags a progressively larger column of water which adheres to the flat end portion of the probe 21 ͑i.e., h max ϳ 2 times fiber diameter͒ creating the hysteresis effect shown in Fig. 3 for the high-k probe.…”
Section: Probe Damping In Watersupporting
confidence: 54%
“…Ref. 21 has suggested that upon initial contact of their nanoneedle probe tip there appears a surface drag or squeeze damping force of the meniscus on the side walls of the probe caused by the large shear rates across the thin meniscus channel. In a separate experiment described in Sec.…”
Section: B Meniscus Model For Probe Damping At the Airwater Interfacementioning
confidence: 99%
See 3 more Smart Citations